Late booking at the Michael Mapongwana antenatal clinic, Khayelitsha – understanding the reasons - De Vaal, Sybrand Johannes (Stellenbosch : University of Stellenbosch, 2015)
Background: The initiation of antenatal care (“booking”) is universally recommended in the first trimester. While working in the Michael Mapongwana antenatal clinic (ANC) in Khayelitsha, the researcher noticed that late booking was prevalent, with consequent impaired antenatal care and increased potential for adverse outcomes. The objective of this qualitative study was to understand why women book late at this specific ANC. Methods: Twenty-three in-depth, open-ended interviews were conducted with 23 late bookers (i.e. who booked after 18 weeks) who attended the ANC between June and October in 2009. The interviews were recorded, transcribed, and analysed according to the “Framework” model. Results: The mean gestational age at booking was 26,4 weeks (range: 20 to 34 weeks). The majority were multigravid, unmarried and unemployed. A high incidence of previous or current obstetric problems was noted. Important personal barriers included ignorance of purpose of antenatal care, ignorance of ideal booking time, and denial or late recognition of an unplanned pregnancy. Provider barriers appeared to be significant, especially the cumbersome booking system, absence of an ultrasound service, and perceived poor quality of care. Conclusion: A combination of personal and provider barriers contributed to late booking at this clinic - it seems that the perceived effort of attending this antenatal service outweighed the perceived value thereof. Provider barriers should be addressed by accommodating patients’ needs, optimising nurse-patient interaction, provision of an ultrasound service and improvement of the booking system. Public awareness of early booking and the holistic value of antenatal care should also be enhanced.